Genetic and functional analysis of the von Hippel-Lindau (VHL) tumour suppressor gene promoter. Issue 7 (1st July 2002) - Zatyka, M; Morrissey, C; Kuzmin, I; Lerman, M I; Latif, F; Richards, F M; Maher, E R
Abstract : The VHL gatekeeper tumour suppressor gene is inactivated in the familial cancer syndrome von Hippel-Lindau disease and in most sporadic clear cell renal cell carcinomas. Recently the VHL gene product has been identified as a specific component of a SCF-like complex, which regulates proteolytic degradation of the hypoxia inducible transcription factors HIF-1 and HIF-2. pVHL is critical for normal development and mRNA expression studies suggest a role in nephrogenesis. Despite the importance of VHL in oncogenesis and development, little is known about the regulation of VHL expression. To investigate VHL promoter activity, we performed comparative sequence analysis of human, primate, and rodent 5' VHL sequences. We then proceeded to deletion analysis of regions showing significant evolutionary conservation between human and rat promoter sequences, and defined two positive and one negative regulatory regions. Analysis of specific putative transcription factor binding sites identified a functional Sp1 site, which was shown to be a regulatory element. Overlapping Sp1/AP2 sites were also identified and candidate E2F1 binding sites evaluated. Three binding sites for as yet unidentified transcription factors were mapped also. These investigations provide a basis for elucidating the regulation of VHL expression in development, the molecular pathology of epigenetic silencing of VHL in tumourigenesis, and suggest a possible link between Sp1, VHL, and nephrogenesis.